Forecasting the Vietnam index of industrial production through the VAR model - Le, Thuyet Huy
Abstract (The aim of this study was to forecast to IIP of Vietnam for selected industries through VAR modeling, standard modeling procedure used in time series analysis because of its simplicity and usefulness. Four IIPs were forecasted: overall IIP of industries, IIP of the manufacturing or processing industry, industry section C, IIP of the electricity production and distribution industry, industry section D; and IIP of the water and gas industry, industry section E. The VAR models used in this study were limited to the VAR and VAR models. Four leading economic indicators were included in the VAR models but the purpose of the study was not to forecast them but to improve the forecasts of IIP by incorporating their influence on the IIP in the different VAR models considered. These leading economic indicators included oil price